Geomorphology of the Montejunto massif (Portugal) - Fonseca, André F. (2011)
The present paper describes a geomorphological map of the Montejunto massif protected area located approximately 50 km to the north of Lisbon, Portugal. The map is based on large-scale field surveys at the scale of 1:10,000 and is published at the scale of 1:20,000. Symbols and legend organization follow the work of Tricart (1970) and Pellegrini et al. (1993). Landforms and processes are grouped according to their morphogenesis and are represented with different colours: Brown – Structural and tectonic-controlled landforms; Purple – Karst and fluvio-karst landforms and deposits; Red – Gravity-induced landforms and processes; Green – Landforms, processes and deposits formed by running water; Blue – Hydrography; Black and Grey – Anthropogenic landforms. The objective of this map is to provide information on the landforms and deposits present in the protected area, allowing it to be used as a baseline for the study of landscape evolution or support guidelines for territorial management and planning.